2022
DOI: 10.1007/s10072-022-06166-w
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET in the differential diagnosis of degenerative parkinsonian disorders: usefulness of voxel-based analysis in clinical practice

Abstract: Background The early differential diagnosis among neurodegenerative parkinsonian disorders becomes essential to set up the correct clinical-therapeutic approach. The increased utilization of [18F] fluoro-deoxy-glucose positron emission tomography (FDG PET) and the pressure for cost-effectiveness request a systematic evaluation and a validation of its utility in clinical practice. This retrospective study aims to consider the contribution, in terms of increasing accuracy and increasing diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Thus, a considerable fraction of the between-reader variability can be explained by intra-reader variability, indicating that visual reading of brain FDG-PET for the detection of PSP is difficult, even when supported by voxel-based testing. This is in line with previous studies that reported lower accuracy of non-expert readers than expert readers regarding the detection of PSP in FDG-PET, 47 and lower accuracy and confidence of expert readers for the detection of PSP compared to the detection of Parkinson's disease or multiple system atrophy. 47 Intra-reader and between-reader stability were considerably better in PSP-RS compared to vPSP.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, a considerable fraction of the between-reader variability can be explained by intra-reader variability, indicating that visual reading of brain FDG-PET for the detection of PSP is difficult, even when supported by voxel-based testing. This is in line with previous studies that reported lower accuracy of non-expert readers than expert readers regarding the detection of PSP in FDG-PET, 47 and lower accuracy and confidence of expert readers for the detection of PSP compared to the detection of Parkinson's disease or multiple system atrophy. 47 Intra-reader and between-reader stability were considerably better in PSP-RS compared to vPSP.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous studies that reported lower accuracy of non-expert readers than expert readers regarding the detection of PSP in FDG-PET, 47 and lower accuracy and confidence of expert readers for the detection of PSP compared to the detection of Parkinson's disease or multiple system atrophy. 47 Intra-reader and between-reader stability were considerably better in PSP-RS compared to vPSP. Among the patients with vPSP, intra-reader variability was larger for cortical vPSP than for subcortical vPSP.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patterns of both brainstem and cortical hypometabolism can also aid in the differentiation of PSP-RS from the parkinsonian disorders, multiple system atrophy (MSA) and Parkinson's disease (PD) [11]. Visual assessment of patterns of hypometabolism performed well in another study, providing 90% accuracy to differentiate clinically diagnosed PSP from CBS, MSA and PD [12]. However, in that study, accuracy to identify CBS was poor at only 50%.…”
Section: Atrophy and Hypometabolismmentioning
confidence: 95%